AMP-activated protein kinase suppresses the in vitro and in vivo proliferation of hepatocellular carcinoma. - Jidong Cheng; Tianliang Huang; Youfeng Li; Yubai Guo; Yuzhang Zhu; Qingjia Wang; Xiaojun Tan; Weisheng Chen; Yongneng Zhang; Weijie Cheng; Tetsuya Yamamoto; Xubin Jing; et al. (PLoS ONE, 2014)
AMP-activated protein kinase (AMPK) is a central metabolic sensor and plays an important role in regulating glucose, lipid and cholesterol metabolism. Therefore, AMPK is a key therapeutic target in diabetes. Recent pilot studies have suggested that diabetes drugs may reduce the risk of cancer by affecting the AMPK pathway. However, the association between AMPK and the proliferation of hepatocellular carcinoma (HCC) is unknown. In this study, we investigated the relationship between AMPK activity and the proliferation of HCC in cell lines, nude mice and human clinic samples. We first investigated the relationship between AMPK activity and cell proliferation in two HCC cell lines, PLC/PRF/5 and HepG2, by two AMPK activators, 5-aminoimidazole-4-carboxamide-1-h-D-ribofuranoside (AICAR) and metformain. AICAR and metformin treatment significantly inhibited the proliferation of HCC cells and induced cell cycle arrest at G1-S checkpoint. We then observed that metformin abrogated the growth of HCC xenografts in nude mice. The clinical pathology of AMPK activity in HCC, including cell proliferation, differential grade, tumor size and microvessel density, was studied by using 30 clinical tissue samples. In HCC tissue samples, phosphorylated AMPK was expressed mainly in cytoplasm. AMPK activity decreased significantly in HCC in comparison with paracancerous liver tissues (P<0.05). AMPK activity was negatively correlated with the level of Ki-67 (a marker of cell proliferation), differential degradation and tumor size (P<0.05), but not with microvessel density, hemorrhage or necrosis in HCC. Our findings suggest that AMPK activity inhibits the proliferation of HCC and AMPK might be an effective target for prevention and treatment of HCC.